Analysis of Wheat Virome in Korea Using Illumina and Oxford Nanopore Sequencing Platforms - Hyo-Jeong Lee; Sang-Min Kim; Rae-Dong Jeong (Plants, 2023)
Wheat (Triticum aestivum L.) is one of the most important staple crops in the world, along with maize and rice. More than 50 plant viruses are known to infect wheat worldwide. To date, there are no studies on the identification of viruses infecting wheat in Korea. Therefore, we investigated virome in wheat from three different geographical regions where wheat is mainly cultivated in Korea using Oxford Nanopore Technology (ONT) sequencing and Illumina sequencing. Five viral species, including those known to infect wheat, were identified using high-throughput sequencing strategies. Of these, barley virus G (BVG) and Hordeum vulgare endornavirus (HvEV) were consistently present in all libraries. Sugarcane yellow leaf virus (SCYLV) and wheat leaf yellowing-associated virus (WLYaV) were first identified in Korean wheat samples. The viruses identified by ONT and Illumina sequencing were compared using a heatmap. Though the ONT sequencing approach is less sensitive, the analysis results were similar to those of Illumina sequencing in our study. Both platforms served as reliable and powerful tools for detecting and identifying wheat viruses, achieving a balance between practicality and performance. The findings of this study will provide deeper insights into the wheat virosphere and further help improve disease management strategies.